Taching Critical Thinking In Reading By Using Three Stay One Stray - Muhlisin, Muhammad; Imran, Fathurrahman (Jurnal Ilmiah Mandala Education (JIME), 2021)
This research was aimed to find out The Effect of Three Stay One Stray towards Students’ Critical Thinking in Reading at MTs NW Darusollihin Kalijaga. The subject of this study was 51 students at second grade of MTs NW Darusollihin Kalijaga. The gorup divided to two classes; they were experiment and control class. 26 students in experimental class and 25 students in control class. In which experiment class consists of 12 males and 14 females and in control class consists of 10 males and 15 females. The researcher gave the critical thinking in reading test by using Three Stray One Stray Strategy to find the students’ critical thinking in reading. In analyzing the data the researcher used descriptive statistics and infrential statistics. Based on the data analysis was gotten that t-test was higher than t-table (5.325 > 1.753)with signification level 5%. Therefore alternative hypothesis accepted and null hypothesis  rejected. Therefore, it concluded that there was significant effect of Three Stay One Stray towards Students’ Critical Thinking in Reading at MTs NW Darusollihin Kalijaga.